2021
DOI: 10.3390/ijerph18157929
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Social Skills and Happiness: Differences by Gender

Abstract: This study examines the relationship between social skills and happiness in 1st-year Teaching School students, as well as possible gender differences. The sample comprised 243 Teaching School students (Primary Education) in Zaragoza, including 110 men (45.27%) and 133 women (54.73%), aged 18–25 (average age 20.23 years; s.d. = 1.586). In order to analyse the relationship between social skills and subjective happiness, the Scale of Social Skills and Subjective Happiness Scale were used. While men scored higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
1
7
0
2
Order By: Relevance
“…The happiness of female civil servants was observed to be higher than that of their male counterparts. This finding is consistent with the findings of Salavera et al and Wang [ 61 , 62 ]. In traditional Chinese society, men are considered to be more stressed than women in both work and life, as men are traditionally given more responsibilities than women, thereby lowering their happiness.…”
Section: Discussionsupporting
confidence: 94%
“…The happiness of female civil servants was observed to be higher than that of their male counterparts. This finding is consistent with the findings of Salavera et al and Wang [ 61 , 62 ]. In traditional Chinese society, men are considered to be more stressed than women in both work and life, as men are traditionally given more responsibilities than women, thereby lowering their happiness.…”
Section: Discussionsupporting
confidence: 94%
“…Gender and age are two of the sociodemographic variables influencing the development of socioemotional skills that have been explored in various studies. One study highlights that women display higher levels in socioemotional skills [ 9 ], whereas another study shows that it is men who achieve higher levels [ 58 ]. Women show greater levels in understanding and emotional regulation [ 2 ], while men tend to score higher in emotional regulation [ 31 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, some authors have pointed out how the parenting styles used with men and women are different [ 43 , 44 ]. Second, although some studies reported that women report higher levels of social skills and are more concerned about the quality of their interpersonal relationships, others point to the opposite [ 45 , 46 ]. Finally, women tend to score higher than men on tests of positive and negative affects [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%